Preparation, characterization and application of EVA film containing Eu3+ complex with 1-tridecanecarboxylic acid ligand. (13th November 2017) - Dong, Jin; Lin, Baoping
Abstract: In this study, on the basis of complex Eu(DBM)3 Phen which was widely applied in polymer matrices, quaternary complex Eu(DBM)2 Phen(TA) was synthesized by the introduction of 1-tridecanecarboxylic acid (TA). XRD analyses show that Eu(DBM)2 Phen(TA) inclines to amorphization compared with Eu(DBM)3 Phen which is crystal. Ethylene-vinyl acetate (EVA) film doped with Eu(DBM)2 Phen(TA) was prepared by casting method. SEM and AFM analyses show that the compatibility of Eu(DBM)2 Phen(TA) with EVA is better than that of Eu(DBM)3 Phen with EVA. Under the same addition amount of Eu 3+ complexes, visible light transmittance of Eu(DBM)2 Phen(TA)/EVA film is obviously greater than that of Eu(DBM)3 Phen/EVA film, and the fluorescence intensity of Eu(DBM)2 Phen(TA)/EVA film is only slightly lower than that of Eu(DBM)3 Phen/EVA film. With the optimum addition amount of Eu 3+ complexes, the energy conversion efficiency of the polycrystalline silicon solar cell coated with Eu(DBM)2 Phen(TA)/EVA film is improved to 12.14%, and in comparison, that of the solar cell coated with Eu(DBM)3 Phen/EVA film is only 11.98%. Hence Eu(DBM)2 Phen(TA)/EVA film has a potential prospect as luminescent down-shifting material.